Student representations on assessment modalities and practices in the subject of history, geography and social sciences, in public education institutions, vulnerable and frontier - Velásquez Parraguez, Eduardo Alejandro (2020)
The research explores the representations of the students on the modalities and evaluative practices used in the subject of History and Geography, of public, vulnerable establishments of a border region. The study is qualitative, employing interpretive techniques in order to explore the representations around the evaluative practices. Information gathering was established through in-depth interviews. The results reported that the main issues identified were a dynamic conception of learning, a complex look at evaluation that includes attitudinal values and a representation of the teacher as an agent that makes institutional evaluation criteria more flexible in response to learning objectives.